Traditional Arid Lands Agriculture : Understanding the Past for the Future - Ingram, Scott E.; Hunt, Robert C. (Book collections on Project MUSE., 2015)
"The manuscript is an edited volume which consists of twelve chapters by multiple scholars of arid lands agriculture in the American Southwest and Northwest Mexico. Its goal is to inspire further research and advance the current understanding of traditional agriculture in arid lands, in both the past and the present"--Provided by publisher